The Influence of Service Quality and Social Media on Consumer Satisfaction - Sofian Nurhasan; Dudi Hendaryan (Almana : Jurnal Manajemen dan Bisnis, 2021)
Consumer Satisfaction is part of the elements inherent in consumers. Currently, there are several alternatives to ensure customer satisfaction, including Service Quality and Social Media. The purpose of this research is to find out how Service Quality, Social Media, and Consumer Satisfaction are applied by the Selly Keyboard at the Dreamscometrue Online Business Community. And to find out how much influence Service Quality has on Consumer Satisfaction, Whatsapp Business Social Media on Consumer Satisfaction, and the influence of Service Quality and Social Media on Consumer Satisfaction. This research is a sample study where consumers are respondents in the study, for data collection using a questionnaire with a total of 88 respondents. The method used is a quantitative method with descriptive analysis and verification analysis. The analysis technique uses path analysis and hypothesis testing. The results of the study stated that Service Quality was in a good category, Social Media was in the quite good category, and Consumer Satisfaction was in a good category. The T-Test results show that Service Quality has an effect on Consumer Satisfaction, Social Media has an effect on Consumer Satisfaction. The F-test shows that Service Quality and Social Media affect Consumer Satisfaction.